2019
DOI: 10.1111/aogs.13595
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends of adverse pregnancy outcomes with maternal age in primipara with singleton birth: A join point analysis of a multicenter historical cohort study in China in 2011‐2012

Abstract: Introduction Adverse pregnancy outcomes are related to two opposite maternal factors, youth and aging. However, the change in trend of specific outcomes with childbearing age is unknown. The aim of this study was to investigate the changing trend of various maternal and neonatal outcomes with maternal age from 17 to 44 years. Material and methods Data were extracted from the medical records from 2011‐2012 of 39 public hospitals of 14 cities in China. The eligibility criteria were primiparity and singleton birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…In our study, at the same time, younger and older age was associated with higher adjusted odds ratios of PE, IUGR, and preterm birth <37th week, which is consistent with reports in the literature [17][18][19]32], but the number of PE (n = 24) and IUGR (n = 21) cases in our the cohort was small. PE and IUGR often coexist, and in their pathogenesis the role of placental ischemia in early pregnancy is taken into account.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, at the same time, younger and older age was associated with higher adjusted odds ratios of PE, IUGR, and preterm birth <37th week, which is consistent with reports in the literature [17][18][19]32], but the number of PE (n = 24) and IUGR (n = 21) cases in our the cohort was small. PE and IUGR often coexist, and in their pathogenesis the role of placental ischemia in early pregnancy is taken into account.…”
Section: Discussionsupporting
confidence: 92%
“…Our core results (higher risk of pregnancy complications in older mothers, and associations of young age with some pregnancy outcomes) are consistent with several reports in the world literature [4,[17][18][19][20][21]28]. However, some studies have found no correlation between maternal age and pregnancy outcomes [2,22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Characteristics of pregnant women, sTBA levels, and PTB rates. Among the characteristics of the subjects, maternal age [20][21][22][23] , and pre-pregnancy body mass index (BMI) [24][25][26][27] had significant impacts on PTB. We performed correlation analyses between sTBA concentrations and PTB rates in subjects with different maternal ages or pre-pregnancy BMIs.…”
Section: Resultsmentioning
confidence: 99%